Hubungan Pola Makan Dengan Aktivitas Olahraga Pada Pasien Diabetes Mellitus Tipe 2 Di Wilayah Kerja Puskesmas Berbah Sleman - Santoso, Rudy; Chasanah, Siti Uswatun; Muryani, Muryani (Jurnal Kesehatan Masyarakat, 2014)
Background:. Diabetes is the fourth leading cause of death in the world. Every year there are 3.2 million deaths caused by diabetes. That means there is 1 person per ten seconds or 60 people per minute are dying from DM. In the United States that have been developed though, the death rate from diabetes could reach 200,000 people a year. Data from Sleman district health profile in 2010 patients with DM who were treated in the clinic as many as 21 867 cases and the results of preliminary studies in PHC Berbah in 2012 there were 968 cases and 704 of them suffering from type 2 diabetes milletus Objective: To know the relationship of diet and exercise activity in patients with type 2 DM in Puskesmas Berbah Sleman, Yogyakarta. Methods: Including observational analytic study using cross-sectional research design. The method used in the sampling in this study is the accidental sampling method. Data analysis was performed using the Spearman rank error level of 5% (0,05). Results: The correlation of test results using statistical test tekhik Spearman Rank Correlation Sig. (2-tailed) = 0.000, which indicates 0.000